Caracterização química do cultivar UPFA 20 Teixerinha, secagem e condições de armazenamento na qualidade industrial de aveia - Simioni, Daniel (2005)
The objective of this work is to characterize chemically the UPFA 20 Teixeirinha cultivar and evaluate the combined effect of drying air temperature, final humidity and storage environmental condition in conservation and industrial quality of stored grains in conventional system for eight for eight months. UPFA 20 Teixeirinha cultivar oat grains were used, 2003/2004 crop and evaluated chemical composition, fatty acid composition, aminoacid in composition, chemical score, metabolic energy, drying air temperature, final humidity and energy consumption. During the oat storage in controlled and not controlled environmental conditions were evaluated periodically in grains with ethereal extract, acidity, fatty acid, humidity, hectolitre weight, characterization of the cultivar was established. In the second experiment the energetic performance was evaluated during the intermittent drying process in different temperatures of drying air and final humidity. In the third experiment the combined effect of the variable drying temperatures, final humidity and storage environmental conditions in the conservation and industrial quality of stored oat were analyzed. The experiments were performed in totally randomized, using 3 x 3 x 2 (drying air temperature; final humidity and storage environmental condition). The results were analyzed statically by both the use of variances analyses (Anova) and in the significant models the averages by Duncan test at the probability of 5%. The intermittent drying when realized in less drastic temperature condition is an efficient method of conservation of both biological and technological parameters of quality in white oat grains. Oat grains with humidity around of 15% present better conservation when stored in controlled environmental condition. The lipids degradation and acidity’s increase during the storage are bigger in dry grains in intermittent process with air at 105 ± 5 ºC. Drying intermittent even with air temperatures up to 105 ± 5 ºC don’t create the metabolic stabilization. The drying air temperature and both initial e final humidity are determining factors to evaluate the energetic consumption and oat grain drying rate.